Putative new plant viruses associated with Plasmopara viticola‐infected grapevine samples. (10th January 2020) - Chiapello, Marco; Rodríguez‐Romero, Julio; Nerva, Luca; Forgia, Marco; Chitarra, Walter; Ayllón, Maria A.; Turina, Massimo
Abstract: In this study, we analysed a total of 16 libraries from over 150 grapevine leaf and grape samples infected with Plasmopara viticola (downy mildew of grapevine) to characterise the virome associated to this oomycete. Samples were collected in five distinct regions in Italy and in four different regions in Spain, representative of different pedoclimatic conditions and different grapevine cultivars during 2018 growing season. Due to the metagenomics nature of the samples (containing at least both downy mildew hyphae and spores, and grapevine cells residues), we were able to assemble several plant viruses and a few possible novel plant virus genomes with our in silico analysis. We detected several plant virus variants already reported in grapevine, and a putative new ilarvirus previously unreported in grapevine. Furthermore, we characterised three new phenui‐like viruses (in the order Bunyavirales ), one of which shares some commonalities with plant coguviruses. Finally, we report a new strict association of three viral segments (one flavi‐like and two virga‐like) that we propose to be a new virus taxon named jivivirus.